Protein kinase C activity and isoform expression during early postnatal development of rat myocardium - Hamplova, B; Novakova, O; Tvrzicka, E; Kolar, F; Novak, F (Cell biochemistry and biophysics, 2005)
Total protein kinase C (PKC) activity, its isoform expression, and concentration and fatty acid (FA) composition of diacylglycerol (DAG) were determined in the left ventricular myocardium of the rat during early postnatal development (d 2, 3, 5, 7, and 10). PKC activity measured by the incorporation of 32P into histone IIIS decreased between d 2 and 10 in the homogenate as well as in cytosolic, membrane (100,000 g), and nuclear-cytoskeletal-myofilament fractions (1000 g). Likewise, the expression of PKC isoforms (alpha, delta, and epsilon) determined by immunoblotting generally declined during the period analyzed, although with a variable pattern. In the membrane and nuclear cytoskeletal myofilament fractions, PKCdelta and PKCepsilon expression decreased markedly by d 3, returning to or close to the d 2 level immediately on d 5. PKCalpha expression in the membrane fraction remained almost unchanged by d 7, declining thereafter. PKCdelta and PKCepsilon were associated predominantly with particulate fractions, whereas PKCalpha was more abundant in the cytosolic fraction. DAG concentration exhibited a significant decline by d 5, consistent with the decrease in maximal PKC activity. The unsaturation index of FA in DAG tended to decrease on d 3 owing to the lowered proportion of all polyunsaturated FA of n-6 and n-3 series. These results demonstrate that the developmental decrease in PKC activity and expression in the rat myocardium is not linear and that subcellular localization of the enzyme exhibits isoform-specific day-by-day changes during the early postnatal period. These changes are compatible with the view that PKC signaling may be involved in the control of a rapid switch of myocardial growth pattern during the first week of life.
Keywords: regulace genové exprese enzymů; tkáňová distribuce; stárnutí; krysa rodu Rattus; zvířata; Enzyme Activation; Aging; potkani Wistar; Gene Expression Regulation, Developmental; Isoenzymes; Rats, Wistar; Male; izoenzymy; Protein Kinase C; Rats; Gene Expression Regulation, Enzymologic; myokard; vývojová regulace genové exprese; proteinkinasa C; Animals; aktivace enzymů; Myocardium; mužské pohlaví; Tissue Distribution